1997
DOI: 10.1016/s0741-5214(97)70223-4
|View full text |Cite
|
Sign up to set email alerts
|

Cellular content and permeability of intraluminal thrombus in abdominal aortic aneurysm

Abstract: These principally structural studies support the hypothesis that the thrombus is a self-sustaining entity that may have significance in the pathophysiologic mechanism of abdominal aortic aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
196
1
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 202 publications
(213 citation statements)
references
References 20 publications
11
196
1
5
Order By: Relevance
“…Specifically, the ILT is stiffer at the luminal layer (c ¼ 2.62 kPa) and gradually softens towards its abluminal site (c ¼ 1.73 kPa) [40], which was accounted for in this study. Finally, it should be noted that although ITL tissue is highly porous [46], previous studies have demonstrated that a single-phase model predicts AAA wall stress with sufficient accuracy [25,26].…”
Section: Constitutive Abdominal Aortic Aneurysm Tissue Modellingmentioning
confidence: 97%
“…Specifically, the ILT is stiffer at the luminal layer (c ¼ 2.62 kPa) and gradually softens towards its abluminal site (c ¼ 1.73 kPa) [40], which was accounted for in this study. Finally, it should be noted that although ITL tissue is highly porous [46], previous studies have demonstrated that a single-phase model predicts AAA wall stress with sufficient accuracy [25,26].…”
Section: Constitutive Abdominal Aortic Aneurysm Tissue Modellingmentioning
confidence: 97%
“…Similarly, the observations of Lendon et al 83 that the mechanical strength of plaque caps is reduced with increased presence of macrophages may be caused by the stimulation of these cells by a local hypoxic environment, 95 causing them to release MMPs 82,93,94 or other proteolytic enzymes. Our laboratory has demonstrated that macrophages are present within the ILT 96 and are exposed to a hypoxic environment. 19,97 The observation by Jean-Claude et al that elevated levels of plasmin are present in the inner layers of the AAA wall near the interface with intraluminal thrombus is a possible consequence of this.…”
Section: Hypoxia-mediated Wall Weakeningmentioning
confidence: 99%
“…10 Recent studies suggest that the ILT is an active pathogenic factor for AAA. [11][12] Adolph et al, 11 have demonstrated the biological activity of the thrombus by the presence of activated cells and by the relative permeability of the aneurismatic wall to formed elements of the blood. Fontaine et al 12 have indicated the enzymatic activity concentrated in mural thrombi as a likely relevant factor in the course of aneurisms.…”
Section: Introductionmentioning
confidence: 99%